Chronic illnesses and labor market participation in the Arab countries: evidence from Egypt and Tunisia. Issue 2 (3rd July 2022) - Ebaidalla, Ebaidalla M.; Mustafa Ali, Mohammed E.
ABSTRACT : This paper examines the impact of chronic illnesses on labor force participation using labor market surveys data for Egypt and Tunisia. The study also investigates the reverse effect of labor force participation on the incidence of chronic diseases. We adopted the simultaneous equations modeling technique to address the potential endogeneity of chronic illnesses in the labor participation equation. The results reveal that chronically ill people are less likely to participate in the labor force in both Egypt and Tunisia. However, the sub-samples analysis indicates some variations across gender and age groups. Specifically, the effect of chronic illnesses is found to be larger and significant for the male group compared to female counterparts. Likewise, the feedback effect shows that labor force participation exerts negative impact on chronic illness, particularly for the total sample. Moreover, the impact of labor force participation on chronic diseases in elder group is larger compared to its effect in the younger group. The study recommends that policymakers in the Arab countries should endeavor to reduce chronic health conditions in order to boost labor force participation and productivity.